2017
DOI: 10.1007/s12603-016-0835-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and cognitive functioning among middle-aged and older adults

Abstract: Objectives: To describe aerobic physical activity among middle-aged and older adults by their self-reported cognitive decline and their receipt of informal care for declines in cognitive functioning and most common type of physical activity. Design: Cross-sectional study using data from the 2011 Behavioral Risk Factor Surveillance System. Setting: Landline and cellular telephone survey. Participants: 93,082 respondents aged 45 years and older from 21 US states i in 2011. Measurements: Subjective cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…Some previous reports have suggested a positive association. For www.nature.com/scientificreports www.nature.com/scientificreports/ instance, a study conducted in 2,315 cognitively healthy elder participants from CFAS-Wales study showed that PA was positively associated with cognitive function measured by the Cambridge Cognitive Examination battery of neuropsychological tests 29 and a larger observational study carried out in 93,082 respondents ≥45 years old from 21 US states reported that people with self-reported cognitive decline were more frequently inactive than those without this subjective cognitive decline status 30 . Moreover, the study conducted by Xu et al in 27,651 participants (50-85 years old) showed a dose-response relationship between PA and cognitive function 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous reports have suggested a positive association. For www.nature.com/scientificreports www.nature.com/scientificreports/ instance, a study conducted in 2,315 cognitively healthy elder participants from CFAS-Wales study showed that PA was positively associated with cognitive function measured by the Cambridge Cognitive Examination battery of neuropsychological tests 29 and a larger observational study carried out in 93,082 respondents ≥45 years old from 21 US states reported that people with self-reported cognitive decline were more frequently inactive than those without this subjective cognitive decline status 30 . Moreover, the study conducted by Xu et al in 27,651 participants (50-85 years old) showed a dose-response relationship between PA and cognitive function 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, “Alteration in cognitive function,” understood as “any disturbance in the phases of the information process, such as perception, learning, memory, attention, vigilance, reasoning, problem solving, and psychomotor functioning (reaction time, movement time, speed of performance)” ( 40 ) , was present in 53.3% of the patients in the investigation that aimed to characterize hospitalized older adults and associate IPM with sex, age, presence of Diabetes mellitus, systemic arterial hypertension, pain, and physical activity ( 41 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In persons with mild cognitive impairment there is an increase in brain activation after 12 weeks of training (9). Exercise increases mental performance and function in older persons (10)(11)(12)(13). Overall, exercise increases neurogenesis, neuronal maturation, angiogenesis, hippocampal volume and learning and memory in mice (14).…”
Section: From Muscle To Brainmentioning
confidence: 99%